Novel human metapneumovirus with a 180-nucleotide duplication in the G gene. (June 2017) - Piñana, María; Vila, Jorgina; Gimferrer, Laura; Valls, María; Andrés, Cristina; Codina, María Gema; Ramón, Javier; Martín, María Carmen; Fuentes, Francisco; Saiz, Rosario; Alcubilla, Pilar; Rodrigo, Carlos; et al.
Aim: To describe the circulation, genetic diversity and clinical features of human metapneumovirus (HMPV) in pediatric patients that attended the Hospital Universitari Vall d'Hebron, Spain from 2014 to 2016.Materials & methods: Partial G gene was sequenced from laboratory-confirmed HMPV respiratory specimens for subsequent phylogenetic analysis.Results: A total of 121 different samples were HMPV laboratory-confirmed out of 6658 specimens received. The highest circulation was from February to April, with a prevalence of 3%. Different genetic groups within both genotypes were detected at variable levels. A 180-nucleotide duplication was first characterized within the G gene in nine cases, mostly related to lower respiratory-tract infection.Conclusion: This study reported on the circulation of a novel HMPV with a 180-nucleotide duplication in the G gene, but no clinical changes in related cases were observed. Their prevalence increased during the last season suggesting changes in viral features.